Interpersonal emotion regulation in team sport: Mechanisms and reasons to regulate teammates' emotions examined. Issue 4 (8th August 2017) - Campo, Mickaël; Sanchez, Xavier; Ferrand, Claude; Rosnet, Elisabeth; Friesen, Andrew; Lane, Andrew M.
Abstract : The interpersonal dimension of emotion regulation in the field of sport has lately received a burgeoning interest. Nevertheless, how and why athletes regulate their teammates' emotions in competitive setting remains unclear. Across two studies within a team sport context, we uncovered athletes' mechanisms for, and reasons to regulate teammates' emotions during competition. In Study 1, we investigated how rugby ( N = 22 males) players' emotions were self- and interpersonally regulated during games. Findings revealed the emergence of a continuum of self-involvement in the regulatory processes, wherein two forms of emotion regulation co-existed: self-regulation (total self-involvement) and interpersonal regulation, which included co-regulation (partial self-involvement; regulation with others) and extrinsic regulation (no self-involvement; regulation by/of others). In Study 2, we examined the motives that lead rugby ( n = 30 males) players to use interpersonal extrinsic regulation strategies during games. Interview data indicated that players regulated teammates' emotions for altruistic reasons (to help a teammate), egoistic reasons (for one's own benefits), or both. Overall, our findings further knowledge to better understand interpersonal emotion regulation within competitive team sport contexts. From an applied perspective, findings highlight the role that both individual goals and ego involvement may play in optimising efficient interpersonal regulation during competition at team level.